Method for manufacturing electrostatic charge image development toner
Patent Information
- Application Number
- JP2024123316
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-01
- Filing Date
- 2024-07-30
- Publication Date
- 2025-02-14
AI Technical Summary
【0008】 本発明の方法により、高速印刷時の低温定着性及び耐久性に優れた静電荷像現像用トナーが得られる。
Smart Images

Figure 2025022807000001 
Figure 2025022807000002 
Figure 2025022807000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a toner for developing electrostatic images used for developing latent images formed in electrophotography, electrostatic recording, electrostatic printing and the like. [Background technology]
[0002] With the development of electrophotographic systems, there is a demand for the development of toners for developing electrostatic images that can meet the demands of higher image quality, and a method for producing chemical toners that can easily produce toner particles with uniform small particle diameters is being investigated, in comparison with pulverized toners obtained by melt-kneading methods. In addition, there is a demand for toners that have low-temperature fixability that can also be used for high-speed printing, for example, high-speed printing of about 0.5 to 1.0 seconds per sheet in A4 portrait orientation.
[0003] On the other hand, as a binder resin for a toner for developing an electrostatic image, a study has been conducted on the use of a crystalline polyester resin in combination with an amorphous polyester resin using polyethylene terephthalate as a raw material monomer (see Patent Documents 1 and 2). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2019-99699 A [Patent Document 2] Patent Publication No. 2021-67882 Summary of the Invention [Problem to be solved by the invention]
[0005] The low-temperature fixability of the toner is improved by using a crystalline polyester resin in combination with an amorphous polyester resin as a binder resin for the toner, but there is a need to improve the low-temperature fixability so that it can be used for high-speed printing. In particular, when forming toner particles in an aqueous medium, crystalline polyester resin, which is more hydrophobic than amorphous polyester resin, tends to exist inside the toner particles, making it difficult to exhibit quick thermal response at high speeds. On the other hand, if the crystalline polyester resin is unevenly distributed near the surface, the low-temperature fixability during high-speed printing is improved, but durability tends to decrease. However, conventional techniques are insufficient to address these issues.
[0006] The present invention relates to a method for producing a toner for developing electrostatic images, which has excellent low-temperature fixability and durability during high-speed printing. [Means for solving the problem]
[0007] The present invention relates to a method for producing a toner for developing electrostatic images, the method including a process for aggregating resin particles, the resin particles containing a crystalline polyester resin C and an amorphous polyester resin A in the same or different particles, in an aqueous medium to obtain aggregated particles, wherein the crystalline polyester resin C has an ester group concentration of 6.5 mmol / g or more and 12.5 mmol / g or less, and the amorphous polyester resin A is a polycondensate of an alcohol component, a carboxylic acid component, and polyethylene terephthalate. Effect of the Invention
[0008] According to the method of the present invention, a toner for developing electrostatic images having excellent low-temperature fixing properties and durability during high-speed printing can be obtained. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The present invention is a method for obtaining a toner for developing electrostatic images by aggregating resin particles in an aqueous medium using a crystalline polyester resin C having a specific ester group concentration and an amorphous polyester resin A obtained from polyethylene terephthalate (PET). Although the detailed mechanism by which the method of the present invention obtains a toner having excellent low-temperature fixing ability during high-speed printing and excellent durability is not clear, it is presumed as follows.
[0010] From the viewpoint of low-temperature fixing property, it is preferable that the crystalline polyester resin is present in the vicinity of the surface of the toner particles. In the present invention, by using crystalline polyester resin C having a high ester group concentration and high hydrophilicity as the binder resin, it is possible to prevent the crystalline polyester resin from being unevenly distributed inside the particles during toner particle formation in an aqueous medium. On the other hand, in the polycondensation reaction of the alcohol component, the carboxylic acid component, and the PET, the PET is depolymerized and incorporated into the polyester resin chain by the transesterification reaction, but it is not completely randomized, and exists as a unit of a certain length that can be called a PET segment in the amorphous polyester resin A. At this time, the ester group concentration of the PET segment is 10.0 mmol / g, so by using a crystalline polyester resin C with a high ester group concentration similar to that of the PET segment, the interaction between the PET segment and the crystalline polyester resin C via the ester group becomes easier to work, and the crystallization of the crystalline polyester resin C is promoted starting from the PET segment. As a result, the thermal response of the toner is improved, and the toner melts by instantaneous heating during fixing, so that the toner has excellent low-temperature fixing properties even in high-speed printing, and the hardness of the toner can be secured by quick crystallization recovery, so that it is considered that a toner with excellent durability can be manufactured even if the crystalline polyester resin is unevenly distributed near the surface of the toner particles.
[0011] In the present invention, the crystalline polyester resin C is preferably a polycondensate of an alcohol component containing an aliphatic diol and a carboxylic acid component containing an aliphatic dicarboxylic acid compound.
[0012] Examples of the aliphatic diol include ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 1,2-butanediol, 1,3-butanediol, 2,3-butanediol, 1,5-pentanediol, 1,2-pentanediol, 1,3-pentanediol, 2,3-pentanediol, 2,4-pentanediol, 1,6-hexanediol, 1,4-butenediol, 1,7-heptanediol, 1,8-octanediol, neopentyl glycol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, and 1,12-dodecanediol.
[0013] The aliphatic diol has 2 or more carbon atoms, and from the viewpoint of adjusting the ester group concentration, it is preferably 14 or less, more preferably 10 or less, and further preferably 8 or less.
[0014] From the viewpoint of improving the low-temperature fixing property of the toner, the aliphatic diol preferably has a hydroxyl group at the end of the carbon chain, and is more preferably an α,ω-straight-chain alkanediol.
[0015] The content of the aliphatic diol in the alcohol component is preferably 80 mol % or more, more preferably 90 mol % or more, and further preferably 95 mol % or more, and 100 mol % or less.
[0016] Examples of alcohol components other than aliphatic diols include aromatic diols such as alkylene oxide adducts of bisphenol A, bisphenol A, hydrogenated bisphenol A, sorbitol, pentaerythritol, glycerin, trimethylolpropane and other trihydric or higher alcohols.
[0017] Examples of the aliphatic dicarboxylic acid compound include succinic acid (carbon number: 4), fumaric acid (carbon number: 4), adipic acid (carbon number: 6), suberic acid (carbon number: 8), azelaic acid (carbon number: 9), sebacic acid (carbon number: 10), dodecanedioic acid (carbon number: 12), tetradecanedioic acid (carbon number: 14), succinic acid derivatives having an alkyl group or an alkenyl group on the side chain, anhydrides of these acids, and alkyl esters of these acids having a carbon number of 1 to 3. Here, when the aliphatic dicarboxylic acid compound is an alkyl ester, the carbon number of the alkyl group is not included in the above carbon number.
[0018] The carbon number of the aliphatic dicarboxylic acid compound is preferably 4 or more, more preferably 6 or more, and even more preferably 8 or more, and from the viewpoint of adjusting the ester group concentration, it is preferably 14 or less, more preferably 12 or less.
[0019] From the viewpoint of hydrophobicity, the content of the aliphatic dicarboxylic acid compound in the carboxylic acid component is preferably 50 mol % or more, more preferably 60 mol % or more, even more preferably 70 mol % or more, and even more preferably 80 mol % or more, and is 100 mol % or less.
[0020] Examples of other carboxylic acid components include aromatic dicarboxylic acid compounds such as phthalic acid, isophthalic acid, and terephthalic acid, and trivalent or higher carboxylic acid compounds such as trimellitic acid and pyromellitic acid.
[0021] Furthermore, the alcohol component and / or the carboxylic acid component of the crystalline polyester resin C preferably contains a monofunctional monomer from the viewpoint of durability.
[0022] Examples of monofunctional monomers contained in the alcohol component include aliphatic monoalcohols such as capryl alcohol, lauryl alcohol, myristyl alcohol, palmityl alcohol, stearyl alcohol, and behenyl alcohol.
[0023] The carbon number of the aliphatic monoalcohol is preferably 10 or more, more preferably 12 or more, and even more preferably 14 or more from the viewpoint of hydrophobicity, and is preferably 22 or less, more preferably 20 or less, and even more preferably 18 or less from the viewpoint of low-temperature fixability.
[0024] Examples of monofunctional monomers contained in the carboxylic acid component include aliphatic monocarboxylic acids such as capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, and behenic acid, and aliphatic monocarboxylic acid compounds such as alkyl esters of these acids in which the alkyl group has 1 to 3 carbon atoms.
[0025] From the viewpoint of hydrophobicity, the carbon number of the aliphatic monocarboxylic acid compound is preferably 10 or more, more preferably 12 or more, and even more preferably 14 or more, and from the viewpoint of low-temperature fixability, it is preferably 22 or less, more preferably 20 or less, and even more preferably 18 or less. Here, when the aliphatic monocarboxylic acid compound is an alkyl ester, the carbon number of the alkyl group is not included in the above carbon number.
[0026] The content of the monofunctional monomer in the total amount of the alcohol component and the carboxylic acid component is preferably 1 mol % or more, more preferably 3 mol % or more, and even more preferably 5 mol % or more, and from the viewpoint of low-temperature fixability, it is preferably 30 mol % or less, more preferably 20 mol % or less, and even more preferably 15 mol % or less.
[0027] In this specification, macromonomers and hydroxycarboxylic acids are not included in the alcohol component and the carboxylic acid component.
[0028] The equivalent ratio of the carboxy group of the carboxylic acid component to the hydroxyl group of the alcohol component (COOH group / OH group) is preferably 0.8 or more, more preferably 0.9 or more, from the viewpoint of charging stability, and is preferably 1.2 or less, more preferably 1.1 or less, from the viewpoint of low-temperature fixing property.
[0029] The crystalline polyester resin C can be produced, for example, by polycondensing an alcohol component and a carboxylic acid component in an inert gas atmosphere, preferably in the presence of an esterification catalyst, and further, if necessary, in the presence of a cocatalyst, a polymerization inhibitor, etc., at a temperature of preferably 120°C or higher, more preferably 180°C or higher, and preferably 230°C or lower, more preferably 220°C or lower.
[0030] Examples of the esterification catalyst include tin compounds such as dibutyltin oxide and tin(II) 2-ethylhexanoate, and titanium compounds such as titanium diisopropoxybis(triethanolaminate) and titanium dihydroxybis(triethanolaminate). The amount of the esterification catalyst used is preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, and preferably 1.5 parts by mass or less, more preferably 1 part by mass or less, based on 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component. Examples of the co-catalyst for the esterification catalyst include gallic acid. The amount of the co-catalyst used is preferably 0.001 parts by mass or more, more preferably 0.01 parts by mass or more, and preferably 0.5 parts by mass or less, more preferably 0.1 parts by mass or less, based on 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component. Examples of the polymerization inhibitor include tert-butylcatechol. The amount of the polymerization inhibitor used is preferably 0.001 part by mass or more, more preferably 0.01 part by mass or more, and preferably 0.5 part by mass or less, more preferably 0.1 part by mass or less, per 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component.
[0031] In the present invention, the polyester resin may be modified to such an extent that its properties are not substantially impaired. Examples of modified polyester resins include polyester resins grafted or blocked with phenol, urethane, epoxy, or the like by the methods described in JP-A-11-133668, JP-A-10-239903, JP-A-8-20636, etc., and among the modified polyester resins, urethane-modified polyester resins in which polyester resins are urethane-extended with a polyisocyanate compound are preferred.
[0032] From the viewpoint of low-temperature fixing ability and durability during high-speed printing, the ester group concentration of crystalline polyester resin C is 6.5 mmol / g or more, preferably 7.0 mmol / g or more, more preferably 7.5 mmol / g or more, and is 12.5 mmol / g or less, preferably 11.5 mmol / g or less, more preferably 11.0 mmol / g or less.
[0033] In the present invention, the ester group concentration of the polyester resin is calculated from the following formula.
[0034]
number
[0035] (In the formula, A is the total amount (mol) of ester bonds produced when all the raw material monomers of the polyester resin are reacted, and B is the total mass (g) of the raw material monomers constituting the polyester resin. The numbers in parentheses in the formula indicate the units of each value.)
[0036] The softening point of the crystalline polyester resin C is preferably 50°C or higher, more preferably 65°C or higher, and even more preferably 70°C or higher from the viewpoint of durability, and is preferably 140°C or lower, more preferably 120°C or lower, and even more preferably 100°C or lower from the viewpoint of low-temperature fixability during high-speed printing.
[0037] The crystallinity of a resin is represented by a crystallinity index defined as the ratio of the softening point to the maximum endothermic peak temperature measured by a differential scanning calorimeter, that is, the value of [softening point / maximum endothermic peak temperature]. The crystalline resin is a resin having a crystallinity index of 0.6 or more, preferably 0.7 or more, more preferably 0.9 or more, and 1.4 or less, preferably 1.2 or less, more preferably 1.1 or less. On the other hand, an amorphous resin is a resin in which no endothermic peak is observed, or if an endothermic peak is observed, the resin has a crystallinity index of more than 1.4, preferably more than 1.5, more preferably 1.6 or more, or less than 0.6, preferably 0.5 or less. The crystallinity of the resin can be adjusted by the type and ratio of the raw material monomers, and the production conditions (e.g., reaction temperature, reaction time, cooling rate), etc. The maximum endothermic peak temperature refers to the temperature of the peak with the largest peak area among the observed endothermic peaks. In the case of a crystalline resin, the maximum endothermic peak temperature is the melting point.
[0038] From the viewpoint of durability, the melting point of the crystalline polyester resin C is preferably 50°C or higher, more preferably 65°C or higher, and even more preferably 70°C or higher, and from the viewpoint of low-temperature fixability during high-speed printing, it is preferably 130°C or lower, more preferably 120°C or lower, and even more preferably 100°C or lower.
[0039] The acid value of the crystalline polyester resin C is preferably 1 mgKOH / g or more, more preferably 3 mgKOH / g or more, from the viewpoint of low-temperature fixability during high-speed printing, and is preferably 20 mgKOH / g or less, more preferably 15 mgKOH / g or less, from the viewpoint of durability.
[0040] The content of crystalline polyester resin C in the total amount of crystalline polyester resin C and amorphous polyester resin A is preferably 3 mass% or more, more preferably 4 mass% or more, even more preferably 5 mass% or more, even more preferably 8 mass% or more, and even more preferably 15 mass% or more from the viewpoint of low-temperature fixability during high-speed printing, and is preferably 40 mass% or less, more preferably 35 mass% or less, even more preferably 30 mass% or less, and even more preferably 25 mass% or less from the viewpoint of durability.
[0041] The amorphous polyester resin A is a polycondensation product of an alcohol component, a carboxylic acid component, and PET.
[0042] From the viewpoint of low-temperature fixability during high-speed printing, the alcohol component preferably contains an aliphatic diol having 3 to 6 carbon atoms.
[0043] Examples of the aliphatic diol having 3 to 6 carbon atoms include 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 2,3-butanediol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, etc. Among these, 1,2-propanediol or neopentyl glycol is preferred from the viewpoint of low-temperature fixability during high-speed printing.
[0044] From the viewpoint of low-temperature fixability during high-speed printing, the content of the aliphatic diol having 3 to 6 carbon atoms in the alcohol component is preferably 70 mol % or more, more preferably 80 mol % or more, and even more preferably 90 mol % or more, and 100 mol % or less, and when the alcohol component contains a trihydric or higher alcohol, it is preferably 95 mol % or less, more preferably 90 mol % or less. However, the alcohol component here does not include the ethylene glycol unit of PET.
[0045] Examples of other alcohol components include aliphatic diols having 7 or more carbon atoms, alkylene oxide adducts of bisphenol A, aromatic diols such as bisphenol A, hydrogenated bisphenol A, sorbitol, pentaerythritol, glycerin, trimethylolpropane, and other trihydric or higher alcohols.
[0046] From the viewpoint of durability, the carboxylic acid component preferably contains an aromatic dicarboxylic acid compound.
[0047] Examples of the aromatic dicarboxylic acid compound include phthalic acid, isophthalic acid, terephthalic acid, anhydrides of these acids, and alkyl esters of these acids having 1 to 3 carbon atoms.
[0048] The content of the aromatic dicarboxylic acid compound in the carboxylic acid component is preferably 70 mol % or more, more preferably 80 mol % or more, even more preferably 90 mol % or more, and still more preferably 95 mol % or more, and 100 mol % or less, provided that the carboxylic acid component does not include the terephthalic acid unit contained in PET.
[0049] Examples of carboxylic acid components other than aromatic dicarboxylic acid compounds include fumaric acid, maleic acid, succinic acid, succinic acid derivatives substituted with a hydrocarbon group, aliphatic dicarboxylic acids such as glutaric acid, adipic acid, and sebacic acid, trivalent or higher carboxylic acids such as trimellitic acid and pyromellitic acid, anhydrides of these acids, and alkyl esters of these acids having 1 to 3 carbon atoms.
[0050] The alcohol component may appropriately contain a monohydric alcohol, and the carboxylic acid component may appropriately contain a monovalent carboxylic acid compound.
[0051] PET is produced by polycondensation of alcohol and carboxylic acid, and / or by depolymerization of a portion of PET. The ethylene glycol and terephthalic acid are used as raw monomers in the polycondensation reaction and are incorporated into polyester resin. PET is an equimolar polycondensation product of ethylene glycol and terephthalic acid, and the ethylene glycol and terephthalic acid that make up PET are regarded as the alcohol and carboxylic acid components, respectively.
[0052] The PET may be new virgin PET or recycled PET. Recycled PET is made by collecting used PET, washing it as necessary, and separating it from other materials before crushing it. The crushed material is then depolymerized to break it down into monomer units, which are then used to resynthesize the material.
[0053] In the present invention, the PET is preferably a PET having a relatively low IV value, i.e., a low molecular weight, compared to conventionally used PET. By introducing a PET having a low IV value (low molecular weight) into the polyester resin, the depolymerization of the PET proceeds more uniformly.
[0054] From the above viewpoints, the IV value of PET is preferably 0.40 or more, more preferably 0.45 or more, even more preferably 0.50 or more, and even more preferably 0.55 or more, and from the viewpoints of low-temperature fixability and uniformity of depolymerization, it is preferably 0.85 or less, more preferably 0.80 or less, even more preferably 0.75 or less, even more preferably 0.70 or less, and even more preferably 0.65 or less. The IV value is an intrinsic viscosity and is an index of molecular weight. The IV value of PET can be adjusted by the polycondensation time, etc.
[0055] Commercially available PET products with an IV value of 0.40 or more and 0.85 or less include RAMAPET L1 (manufactured by Indorama Ventures, IV value: 0.60), RAMAPET BF3067 (manufactured by Indorama Ventures, IV value: 0.65), RAMAPET N2G (manufactured by Indorama Ventures, IV value: 0.75), TRN-NTJ (manufactured by Teijin Limited, IV value: 0.53), TRN-RTJC (manufactured by Teijin Limited, IV value: 0.64), RAMAPET S1 (manufactured by Indorama Ventures, IV value: 0.84), and UK-31 (manufactured by Utsumi Recycle Systems Co., Ltd., IV value: 0.67).
[0056] The content of the low IV PET in the total amount of PET used in polycondensation is preferably 90% by mass or more, more preferably 95% by mass or more, even more preferably 98% by mass or more, and still more preferably 100% by mass.
[0057] The PET content is preferably 5 mol% or more, more preferably 10 mol% or more, and even more preferably 20 mol% or more, and is preferably 75 mol% or less, more preferably 50 mol% or less, and even more preferably 40 mol% or less, in the total amount of the alcohol component, the carboxylic acid component, and the PET, from the viewpoint of durability. When the amorphous polyester resin A is composed of two or more resins, the weighted average value of the PET contents of the respective resins is defined as the PET content of the amorphous polyester resin A. In addition, since PET is a polycondensation product of ethylene glycol and terephthalic acid, dimethyl terephthalate, etc., the terephthalic acid-ethylene glycol unit (Mw: 192) is calculated as 1 mole. Therefore, the number of moles of PET = the number of moles of ethylene glycol units = the number of moles of terephthalic acid units.
[0058] The equivalent ratio (COOH group / OH group) of the carboxylic acid component (including the terephthalic acid unit in the PET) to the alcohol component (including the ethylene glycol unit in the PET) is preferably 0.6 or more, more preferably 0.7 or more, even more preferably 0.8 or more, and is preferably 1.3 or less, more preferably 1.2 or less.
[0059] The polycondensation reaction conditions of the alcohol component, the carboxylic acid component, and the PET of the amorphous polyester resin are similar to those of the crystalline polyester resin, except that the suitable reaction temperature is preferably 130°C or more, more preferably 170°C or more, and preferably 250°C or less, more preferably 240°C or less.
[0060] The softening point of the amorphous polyester resin A is preferably 70°C or higher, more preferably 90°C or higher, and even more preferably 100°C or higher from the viewpoint of durability, and is preferably 150°C or lower, more preferably 130°C or lower, and even more preferably 120°C or lower from the viewpoint of low-temperature fixability during high-speed printing.
[0061] The glass transition temperature of the amorphous polyester resin A is preferably 40° C. or higher, more preferably 50° C. or higher, from the viewpoint of durability, and is preferably 80° C. or lower, more preferably 70° C. or lower, from the viewpoint of low-temperature fixability during high-speed printing.
[0062] The acid value of the amorphous polyester resin A is preferably 1 mgKOH / g or more, more preferably 3 mgKOH / g or more, from the viewpoint of low-temperature fixability during high-speed printing, and is preferably 20 mgKOH / g or less, more preferably 18 mgKOH / g or less, from the viewpoint of durability.
[0063] The content of amorphous polyester resin A in the total amount of crystalline polyester resin C and amorphous polyester resin A is, from the viewpoint of durability, preferably 60% by mass or more, more preferably 65% by mass or more, more preferably 70% by mass or more, and even more preferably 75% by mass or more, and from the viewpoint of low-temperature fixability during high-speed printing, preferably 97% by mass or less, more preferably 96% by mass or less, even more preferably 95% by mass or less, even more preferably 92% by mass or less, and even more preferably 85% by mass or less.
[0064] The mass ratio of crystalline polyester resin C to amorphous polyester resin A (crystalline polyester resin C / amorphous polyester resin A) is, from the viewpoint of low-temperature fixability during high-speed printing, preferably 3 / 97 or more, more preferably 4 / 96 or more, even more preferably 5 / 95 or more, even more preferably 8 / 92 or more, and even more preferably 15 / 85 or more, and from the viewpoint of durability, is preferably 40 / 60 or less, more preferably 35 / 65 or less, even more preferably 30 / 70 or less, and even more preferably 25 / 75 or less.
[0065] In the toner, the crystalline polyester resin C and the amorphous polyester resin A are contained as binder resins.
[0066] Other examples of the binder resin include vinyl resins such as styrene-acrylic resin, epoxy resin, polycarbonate, polyurethane, and composite resins containing two or more of these resins.
[0067] The total content of the crystalline polyester resin C and the amorphous polyester resin A in the binder resin is preferably 70% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, even more preferably 95% by mass or more, and even more preferably 100% by mass.
[0068] In addition, the content of the binder resin in the toner is preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, and is preferably less than 100% by mass, more preferably 98% by mass or less, even more preferably 95% by mass or less.
[0069] In addition to the binder resin, additives such as colorants, release agents, charge control agents, magnetic powders, flowability improvers, conductivity regulators, reinforcing fillers such as fibrous substances, antioxidants, and cleaning improvers may be used as raw materials for the toner.
[0070] As the colorant, dyes, pigments, magnetic materials, etc. used as colorants for toners can be used. For example, carbon black, phthalocyanine blue, permanent brown FG, brilliant fast scarlet, pigment red 122, pigment green B, rhodamine-B base, solvent red 49, solvent red 146, solvent blue 35, quinacridone, carmine 6B, isoindoline, disazo yellow, etc. can be mentioned. In the present invention, the toner may be either a black toner or a color toner.
[0071] From the viewpoint of improving the image density and low-temperature fixability of the toner, the amount of the colorant used is preferably 1 part by mass or more, more preferably 2 parts by mass or more, and preferably 40 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 15 parts by mass or less, relative to 100 parts by mass of the binder resin.
[0072] Examples of the release agent include hydrocarbon waxes such as polypropylene wax, polyethylene wax, ethylene propylene copolymer wax, microcrystalline wax, paraffin wax, and Fischer-Tropsch wax, and oxides thereof; ester waxes such as carnauba wax, montan wax, and deacidified waxes thereof, and fatty acid ester wax; fatty acid amides, fatty acids, higher alcohols, and fatty acid metal salts. These may be used alone or in combination of two or more.
[0073] The melting point of the release agent is preferably 60° C. or higher, more preferably 70° C. or higher, from the viewpoint of toner transferability, and is preferably 160° C. or lower, more preferably 140° C. or lower, even more preferably 120° C. or lower, and even more preferably 110° C. or lower, from the viewpoint of low-temperature fixability.
[0074] The amount of the release agent used, from the viewpoint of the low-temperature fixability and offset resistance of the toner and the viewpoint of dispersibility in the binder resin, is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, and even more preferably 1.5 parts by mass or more, relative to 100 parts by mass of the binder resin, and is preferably 10 parts by mass or less, more preferably 8 parts by mass or less, and even more preferably 7 parts by mass or less.
[0075] In the present invention, the toner is manufactured by a method including a step (aggregation step) of aggregating resin particles containing crystalline polyester resin C and amorphous polyester resin A in the same or different particles in an aqueous medium to obtain aggregated particles. From the viewpoint of the stability of the toner particles, it is preferable to further include a step (fusion step) of fusing the aggregated particles obtained in the aggregation step to obtain toner particles, and the aggregation step and the fusion step may be carried out in an overlapping manner. The crystalline polyester resin C and the amorphous polyester resin A may be contained in the same particles or in different particles.
[0076] The resin particles can be used as an aqueous dispersion by, for example, dispersing in advance in an aqueous medium a resin component containing a crystalline polyester resin C and / or an amorphous polyester resin A, and, if necessary, optional components such as a colorant, a release agent, etc. (hereinafter, the resin component and the optional components are collectively referred to as "resin component, etc.").
[0077] The aqueous medium is preferably one containing water as a main component, and from the viewpoint of improving the dispersion stability of the aqueous dispersion and from the viewpoint of environmental friendliness, the content of water in the aqueous medium is preferably 80% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, even more preferably 98% by mass or more, and even more preferably 100% by mass. As the water, deionized water or distilled water is preferable.
[0078] Examples of components other than water that may be contained in the aqueous medium include organic solvents that dissolve in water, such as alkyl alcohols having 1 to 5 carbon atoms, dialkyl ketones having 3 to 5 carbon atoms, such as acetone and methyl ethyl ketone, and cyclic ethers, such as tetrahydrofuran. Among these, from the viewpoint of preventing the organic solvent from being mixed into the toner, alkyl alcohols having 1 to 5 carbon atoms that do not dissolve polyester resins are preferred, and methanol, ethanol, isopropanol, or butanol are more preferred.
[0079] Methods for obtaining an aqueous dispersion of resin particles include a method of adding a resin component, etc. to an aqueous medium and performing a dispersion treatment using a disperser, a method of gradually adding an aqueous medium to a melt or an organic solvent solution of the resin component, etc., to cause phase inversion emulsification (phase inversion emulsification), etc. Among these, the phase inversion emulsification method is preferred from the viewpoint of improving the low-temperature fixability and durability of the toner during high-speed printing.
[0080] Examples of the phase inversion emulsification method include a method (A) in which a resin component, etc. is dissolved in an organic solvent to obtain an organic solvent solution of the resin component, etc., and an aqueous medium is added to the obtained solution to perform phase inversion emulsification, or a method (B) in which an aqueous medium is added to a resin mixture obtained by melting and mixing the resin component, etc. From the viewpoint of obtaining a homogeneous aqueous dispersion of resin particles, the method (A) is preferred.
[0081] The organic solvent used in the phase inversion emulsification method preferably has a solubility parameter (SP value: POLYMER HANDBOOK THIRD EDITION 1989 by John Wiley & Sons, Inc.) of 15.0 MPa. 1 / 2 More preferably, 16.0MPa 1 / 2 More preferably, 17.0 MPa 1 / 2 and preferably 26.0 MPa or more. 1 / 2 Less than or equal to 24.0MPa, more preferably 1 / 2 Less than 22.0MPa, more preferably 22.0MPa 1 / 2 Preferred are organic solvents which are:
[0082] Examples of organic solvents include alcohol-based solvents such as ethanol (26.0), isopropanol (23.5), and isobutanol (21.5); ketone-based solvents such as acetone (20.3), methyl ethyl ketone (19.0), methyl isobutyl ketone (17.2), and diethyl ketone (18.0); ether-based solvents such as dibutyl ether (16.5), tetrahydrofuran (18.6), and dioxane (20.5); and acetate-based solvents such as ethyl acetate (18.6) and isopropyl acetate (17.4). The numbers in parentheses after each solvent are the SP values (unit: MPa). 1 / 2 Among these, from the viewpoint of ease of removal from the mixed solution after the addition of the aqueous medium, preferably one or more solvents selected from ketone solvents and acetate solvents, more preferably one or more solvents selected from methyl ethyl ketone, ethyl acetate and isopropyl acetate, and even more preferably methyl ethyl ketone.
[0083] In the phase inversion emulsification method, it is preferable to treat the resin with a neutralizing agent.
[0084] Examples of the neutralizing agent include basic substances, etc. Examples of the basic substance include alkali metal hydroxides such as lithium hydroxide, sodium hydroxide, and potassium hydroxide, and nitrogen-containing basic substances such as ammonia, trimethylamine, ethylamine, diethylamine, triethylamine, diethanolamine, triethanolamine, and tributylamine, and among these, from the viewpoint of improving the dispersion stability and aggregation property of the resin particles, preferably at least one selected from ammonia and alkali metal hydroxides, more preferably at least one selected from ammonia and sodium hydroxide, and even more preferably sodium hydroxide.
[0085] The equivalent amount (mol %) of the neutralizing agent used relative to the acid groups of the resin is preferably 10 mol % or more, more preferably 30 mol % or more, and is preferably 150 mol % or less, more preferably 120 mol % or less, and even more preferably 100 mol % or less. The equivalent amount (mol %) of the neutralizing agent used can be calculated by the following formula. Equivalent amount of neutralizing agent used (mol%) = [{weight of neutralizing agent added (g) / equivalent amount of neutralizing agent} / [{acid value of resin (mg KOH / g) × weight of resin (g)} / (56 × 1000)]] × 100
[0086] From the viewpoint of improving the dispersion stability of the resin particles, the temperature when the aqueous medium is added is preferably 20°C or higher, more preferably 40°C or higher, even more preferably 50°C or higher, and is preferably 90°C or lower, more preferably 80°C or lower, even more preferably 75°C or lower.
[0087] From the viewpoint of obtaining resin particles having a small particle size, the addition rate of the aqueous medium is preferably 0.1 parts by mass / min or more, more preferably 0.5 parts by mass / min or more, even more preferably 3 parts by mass / min or more, and preferably 50 parts by mass / min or less, more preferably 30 parts by mass / min or less, even more preferably 20 parts by mass / min or less, even more preferably 10 parts by mass / min or less, based on 100 parts by mass of the resin constituting the resin particles, until the phase inversion is completed. There is no restriction on the addition rate of the aqueous medium after the phase inversion.
[0088] After the phase inversion emulsification, the organic solvent may be removed from the obtained dispersion, if necessary. The organic solvent is preferably removed by distillation since it is dissolved in water. The remaining amount of the organic solvent in the aqueous dispersion is preferably 1% by mass or less, more preferably 0.5% by mass or less, and even more preferably substantially 0% by mass.
[0089] The content of the resin in all the resin components contained in the resin particles is preferably 80% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, and still more preferably 100% by mass.
[0090] From the viewpoint of improving the productivity of the toner and the dispersion stability of the aqueous dispersion of the resin particles, the solid content concentration of the aqueous dispersion of the resin particles is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 15% by mass or more, and is preferably 50% by mass or less, more preferably 40% by mass or less, even more preferably 30% by mass or less, and even more preferably 25% by mass or less. The solid content is the total amount of non-volatile components such as the resin, colorant, surfactant, etc.
[0091] The resin content in the solid content of the aqueous dispersion of resin particles is preferably 80% by mass or more, more preferably 85% by mass or more, and even more preferably 90% by mass or more, and 100% by mass or less.
[0092] The volume median diameter (D 50 ) is preferably 0.05 μm or more, more preferably 0.10 μm or more, even more preferably 0.12 μm or more, and is preferably 0.80 μm or less, more preferably 0.40 μm or less, even more preferably 0.30 μm or less. In addition, the CV value of the resin particles is preferably 5% or more, more preferably 15% or more, and even more preferably 20% or more, from the viewpoint of improving the productivity of the aqueous dispersion of the resin particles, and is preferably 50% or less, more preferably 40% or less, and even more preferably 35% or less, from the viewpoint of obtaining a toner that can produce high-quality images. In the present invention, the CV value is calculated according to the following formula. CV value (%) = (Standard deviation of particle size distribution / Volume average particle size) x 100
[0093] As described above, the optional components such as a colorant, a release agent, etc. may be mixed with the resin when preparing the aqueous dispersion of the resin particles, or a dispersion in which each of the optional components is dispersed in an aqueous medium may be separately prepared and mixed with the aqueous dispersion of the resin particles to obtain aggregated particles.
[0094] For example, an aqueous dispersion of a release agent (release agent dispersion) is preferably obtained by dispersing release agent particles in a mixture of a release agent and an aqueous medium at a temperature equal to or higher than the melting point of the release agent using a disperser.
[0095] The dispersion of the release agent particles in an aqueous medium is preferably carried out in the presence of a surfactant from the viewpoint of improving the dispersion stability of the release agent particles and from the viewpoint of obtaining uniformly aggregated particles.
[0096] Examples of the surfactant include anionic surfactants such as sodium dodecylbenzenesulfonate, sodium dodecyl sulfate, sodium lauryl ether sulfate, and dipotassium alkenylsuccinate; cationic surfactants; and nonionic surfactants.
[0097] The content of the surfactant in the release agent dispersion liquid is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, and even more preferably 0.5% by mass or more, from the viewpoint of improving the dispersion stability of the release agent particles and from the viewpoint of improving the aggregation properties of the release agent particles during toner production and preventing them from becoming detached, and is preferably 5.0% by mass or less, and more preferably 3.0% by mass or less.
[0098] Examples of the dispersing machine that can be used include a homogenizer, an ultrasonic dispersing machine, and a high-pressure dispersing machine.
[0099] In addition, before using the dispersing machine, it is preferable to preliminarily disperse the optional components, the surfactant, and the aqueous medium in a mixer such as a homomixer or a ball mill. The aqueous medium used for the optional components is the same as the aqueous medium used for obtaining the aqueous dispersion of the resin particles.
[0100] From the viewpoint of improving the productivity of the toner and the dispersion stability of the release agent particles, the solid content concentration of the release agent dispersion liquid is preferably 5% by mass or more, more preferably 10% by mass or more, even more preferably 15% by mass or more, and is preferably 50% by mass or less, more preferably 30% by mass or less, even more preferably 25% by mass or less.
[0101] Volume median particle size of release agent particles (D 50 From the viewpoint of obtaining uniform aggregated particles, the average particle diameter is preferably 0.10 μm or more, more preferably 0.20 μm or more, even more preferably 0.30 μm or more, and is preferably 1.0 μm or less, more preferably 0.80 μm or less, even more preferably 0.60 μm or less.
[0102] Similarly to the release agent dispersion, the water-based dispersion of the colorant (colorant dispersion) is preferably obtained by dispersing colorant particles using a disperser, preferably in the presence of a surfactant.
[0103] The surfactant used in the preparation of the colorant dispersion liquid includes nonionic surfactants, anionic surfactants, cationic surfactants, etc., and from the viewpoint of improving the dispersion stability of the colorant particles and the aggregation property between the colorant particles and the resin particles, anionic surfactants are preferred. Specific examples of the surfactant include sodium dodecylbenzenesulfonate, sodium dodecyl sulfate, sodium lauryl ether sulfate, dipotassium alkenyl succinate, etc., and sodium dodecylbenzenesulfonate is preferred.
[0104] The content of the surfactant in the colorant dispersion liquid is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and even more preferably 1.0% by mass or more, from the viewpoint of improving the dispersion stability of the colorant particles and improving the aggregation properties of the colorant particles during toner production and preventing them from becoming free, and is preferably 5.0% by mass or less, and more preferably 4.5% by mass or less.
[0105] From the viewpoint of improving the productivity of the toner and the dispersion stability of the aqueous dispersion of colorant particles, the solids concentration of the colorant dispersion is preferably 5% by mass or more, more preferably 10% by mass or more, even more preferably 15% by mass or more, and is preferably 50% by mass or less, more preferably 40% by mass or less, even more preferably 30% by mass or less.
[0106] Volume median particle size of colorant particles (D 50 From the viewpoint of obtaining a toner that can provide high-quality images, the particle size is preferably 0.05 μm or more, more preferably 0.08 μm or more, even more preferably 0.10 μm or more, and is preferably 0.50 μm or less, more preferably 0.30 μm or less, even more preferably 0.15 μm or less.
[0107] In the aggregating step, it is preferable to add an aggregating agent from the viewpoint of efficiently aggregating the resin particles. From the viewpoint of obtaining a toner having a desired particle size while preventing excessive aggregation, the aggregating agent is preferably an electrolyte, and more preferably a salt. Examples of the aggregating agent include organic aggregating agents such as quaternary salt cationic surfactants and polyethyleneimine; and inorganic aggregating agents such as inorganic metal salts, inorganic ammonium salts, and divalent or higher metal complexes. Among these, from the viewpoint of improving the aggregating property and obtaining uniform aggregated particles, inorganic aggregating agents are preferred, more preferably inorganic metal salts or inorganic ammonium salts, and even more preferably inorganic ammonium salts.
[0108] The valence of the cation of the inorganic flocculant is preferably 5 or less, more preferably 2 or less, and even more preferably 1, from the viewpoint of obtaining a toner having a desired particle size while preventing excessive aggregation. Examples of the monovalent cation of the inorganic flocculant include sodium ion, potassium ion, and ammonium ion, and among these, the ammonium ion is preferred.
[0109] Examples of inorganic metal salts include metal salts such as sodium sulfate, sodium nitrate, sodium chloride, calcium chloride, and calcium nitrate, and inorganic metal salt polymers such as polyaluminum chloride and polyaluminum hydroxide. Examples of inorganic ammonium salts include ammonium sulfate, ammonium chloride, and ammonium nitrate.
[0110] The flocculant is preferably ammonium sulfate.
[0111] From the viewpoint of controlling aggregation to obtain the desired particle size, the amount of the coagulant used is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and even more preferably 20 parts by mass or more, relative to 100 parts by mass of the resin, and is preferably 50 parts by mass or less, and more preferably 45 parts by mass or less.
[0112] The flocculant is preferably added dropwise to the mixed dispersion. The flocculant may be added all at once, or may be added intermittently or continuously. During and after the addition, it is preferable to carry out sufficient stirring.
[0113] From the viewpoint of controlling aggregation to obtain aggregated particles of a desired particle size, the aggregating agent is preferably added dropwise as an aqueous solution, and the concentration of the aqueous solution of the aggregating agent is preferably 2% by mass or more and 40% by mass or less.
[0114] From the viewpoint of controlling aggregation to obtain aggregated particles having a desired particle size and particle size distribution, it is preferable to use an aqueous solution of the flocculant having a pH adjusted to 7.0 or more and 9.0 or less.
[0115] The dropping time of the flocculant is preferably 1 minute or more and 120 minutes or less from the viewpoint of controlling the flocculation to obtain flocculated particles having a desired particle size.
[0116] The aggregation temperature of the resin particles when the aggregating agent is dropped in the aggregation step is preferably 0° C. or higher and 40° C. or lower, from the viewpoint of controlling the aggregation to obtain aggregated particles having a desired particle size.
[0117] Furthermore, from the viewpoint of promoting aggregation and obtaining aggregated particles having a desired particle size and particle size distribution, it is preferable to raise the temperature of the dispersion after adding the aggregating agent, and the temperature to be maintained is preferably 45° C. or higher, more preferably 50° C. or higher, and preferably 80° C. or lower, more preferably 70° C. or lower, and even more preferably 65° C. or lower.
[0118] The volume median particle size of the resulting agglomerates (D 50) is preferably 2 μm or more, more preferably 3 μm or more, even more preferably 4 μm or more, and is preferably 10 μm or less, more preferably 8 μm or less, even more preferably 7 μm or less.
[0119] The fusion step is a step in which the aggregated particles obtained in the aggregation step are fused to obtain toner particles. The particles in the aggregated particles, which were mainly physically attached to each other, are fused together to form toner particles (fused particles).
[0120] In the fusion step, the temperature is preferably maintained at or above the glass transition temperature of the amorphous polyester resin A from the viewpoints of improving the fusion properties of the aggregated particles and enhancing the low-temperature fixability and durability of the toner during high-speed printing.
[0121] From the viewpoint of improving the fusion property of the aggregated particles and improving the productivity of the toner, the holding temperature is preferably at least 2°C higher than the glass transition temperature of the amorphous polyester resin A, more preferably at least 4°C higher than the glass transition temperature of the amorphous polyester resin A, and is preferably not higher than 30°C higher than the glass transition temperature of the amorphous polyester resin A, more preferably not higher than 25°C higher than the glass transition temperature of the amorphous polyester resin A. By maintaining the fused particles at the above temperature until the desired circularity is reached, the circularity of the toner particles can be controlled.
[0122] The volume median particle size (D 50 From the viewpoint of improving the low-temperature fixing property and durability of the toner, the particle size is preferably 2 μm or more, more preferably 3 μm or more, even more preferably 4 μm or more, and is preferably 10 μm or less, more preferably 8 μm or less, even more preferably 7 μm or less.
[0123] From the viewpoint of improving the low-temperature fixability and durability of the toner, the circularity of the toner particles in the dispersion obtained in the fusion step is preferably 0.955 or more, more preferably 0.960 or more, even more preferably 0.965 or more, and is preferably 0.990 or less, more preferably 0.985 or less, even more preferably 0.980 or less.
[0124] The toner particles obtained in the fusion step are preferably subjected to an appropriate post-treatment step and then isolated. For example, since the toner particles in the dispersion obtained in the fusion step are present in an aqueous medium, it is preferable to first carry out solid-liquid separation. For solid-liquid separation, a suction filtration method or the like is preferably used. It is preferable to wash the solid-liquid separation product. In this case, it is preferable to remove the surfactant added, and therefore it is preferable to wash the product with an aqueous medium at a temperature below the cloud point of the surfactant. It is preferable to wash the product several times.
[0125] Next, drying is preferably performed. The temperature during drying is preferably set so that the temperature of the toner particles themselves is lower than the glass transition temperature of the amorphous polyester resin A. As the drying method, a vacuum low-temperature drying method, a vibration type fluidized drying method, a spray drying method, a freeze drying method, a flash jet method, or the like is preferably used. From the viewpoint of improving the charging characteristics of the toner, the moisture content after drying is preferably adjusted to 1.5% by mass or less, more preferably 1.0% by mass or less.
[0126] In the present invention, it is preferable to further carry out a step of mixing the toner particles obtained in the fusion step with an external additive (external addition step).
[0127] Examples of the external additive used in the external addition step include inorganic fine particles such as silica, alumina, titania, zirconia, tin oxide, and zinc oxide, and organic fine particles such as melamine-based resin fine particles and polytetrafluoroethylene resin fine particles, and two or more of them may be used in combination. Among these, silica is preferred, and from the viewpoint of the transferability of the toner, hydrophobic silica that has been subjected to a hydrophobic treatment is more preferred.
[0128] Examples of hydrophobic treatment agents for hydrophobizing the surface of silica particles include hexamethyldisilazane (HMDS), dimethyldichlorosilane (DMDS), cyclic silazane, silicone oil, aminosilane, octyltriethoxysilane (OTES), and methyltriethoxysilane.
[0129] From the viewpoint of the chargeability, fluidity, and transferability of the toner, the average particle size of the external additive is preferably 10 nm or more, more preferably 15 nm or more, and is preferably 250 nm or less, more preferably 200 nm or less, and even more preferably 90 nm or less.
[0130] The toner particles and the external additives can be mixed in a conventional manner using a mixer such as a Henschel mixer.
[0131] From the viewpoint of the electrostatic chargeability, fluidity, and transferability of the toner, the amount of the external additive used is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, and even more preferably 0.3 parts by mass or more, relative to 100 parts by mass of the toner particles, and is preferably 5 parts by mass or less, and more preferably 3 parts by mass or less.
[0132] The toner for developing electrostatic images obtained by the method of the present invention can be used as a toner for single-component development as it is, or as a toner for two-component development mixed with a carrier, in an image forming apparatus of a single-component development system or a two-component development system, respectively. EXAMPLES
[0133] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. Physical properties of resins and the like can be measured by the following methods.
[0134] [PET IV value] The viscosity is calculated from the following formula: Dissolve the solution at a concentration of 4 g / L in a mixed solvent of phenol / tetrachloroethane at a mass ratio of 60 / 40, measure using an Ubbelohde viscometer, and IV=(-1+√(1+4kη)) / (2kC) (In the formula, k = 0.33, C = 0.004 g / mL, and η = (t1 / t0)-1 (t0: number of seconds for the solvent alone to fall, t1: number of seconds for the sample solution to fall).)
[0135] [Softening point of resin] Using a flow tester "CFT-500D" (Shimadzu Corporation), 1g of sample is heated at a temperature increase rate of 6℃ / min while applying a load of 1.96MPa with the plunger, and extruding the sample from a nozzle with a diameter of 1mm and a length of 1mm. The amount of plunger descent of the flow tester is plotted against the temperature, and the temperature at which half of the sample has flowed out is taken as the softening point.
[0136] [Maximum endothermic peak temperature of resin] Using a differential scanning calorimeter "Q-100" (manufactured by TA Instruments Japan, Inc.), weigh 0.01 to 0.02 g of sample into an aluminum pan, cool from room temperature (25°C) to 0°C at a rate of 10°C / min, and maintain at 0°C for 1 minute. Then, measure at a rate of 10°C / min. The temperature of the peak with the largest peak area among the observed endothermic peaks is regarded as the maximum endothermic peak temperature. For crystalline resins, the maximum endothermic peak temperature is regarded as the melting point.
[0137] [Glass transition temperature of resin] Using a differential scanning calorimeter "Q-100" (manufactured by TA Instruments Japan Co., Ltd.), 0.01 to 0.02 g of sample is weighed into an aluminum pan, heated from room temperature (20°C) to 200°C at a heating rate of 10°C / min, and cooled from that temperature to 0°C at a heating rate of 10°C / min. Next, the sample is heated at a heating rate of 10°C / min and the endothermic peak is measured. The glass transition temperature is the temperature at the intersection of the extension of the baseline below the maximum endothermic peak temperature and the tangent line showing the maximum slope from the rising part of the peak to the top of the peak.
[0138] [Acid value of resin] Measurements are performed based on the method of JIS K 0070:1992, except that the measurement solvent is changed from the ethanol and ether mixture specified in JIS K 0070 to a mixture of acetone and toluene (acetone:toluene = 1:1 (volume ratio)) for amorphous resins, and to a mixture of chloroform and dimethylformamide (chloroform:dimethylformamide = 7:3 (volume ratio)) for crystalline resins.
[0139] [Melting point of release agent] Using a differential scanning calorimeter "Q-100" (manufactured by TA Instruments Japan Co., Ltd.), 0.02 g of sample is weighed into an aluminum pan, heated to 200°C, and then cooled from 200°C to 0°C at a rate of 10°C / min. The sample is then heated at a rate of 10°C / min, the amount of heat is measured, and the maximum endothermic peak temperature is taken as the melting point.
[0140] [Solid Content Concentration of Resin Particle Dispersion, Colorant Particle Dispersion, and Release Agent Particle Dispersion] Using an infrared moisture meter "FD-230" (Kett Electric Laboratory Co., Ltd.), 5 g of the measurement sample is dried at a drying temperature of 150°C and measurement mode 96 (monitoring time 2.5 minutes, fluctuation range 0.05%), and the moisture content (mass%) of the dispersion is measured. The solid content concentration is calculated according to the following formula. Solid concentration (mass%) = 100-moisture (mass%)
[0141] [Volume Median Particle Size and CV Value of Resin Particles, Colorant Particles, and Release Agent Particles] (1) Measuring device: Laser diffraction type particle size measuring device "LA-920" (manufactured by Horiba, Ltd.) (2) Measurement conditions: Put the sample dispersion in a measurement cell, add distilled water, and measure the volume median particle size (D 50 ) and the volume average particle size are measured. The CV value is calculated according to the following formula. CV value (%) = (Standard deviation of particle size distribution / Volume average particle size) x 100
[0142] [Volume Median Particle Size of Agglomerated Particles] Measuring instrument: "Coulter Multisizer (registered trademark) III" (manufactured by Beckman Coulter, Inc.) Aperture diameter: 50μm Analysis software: "Multisizer (registered trademark) III version 3.51" (Beckman Coulter, Inc.) Electrolyte: "Isoton (registered trademark) II" (manufactured by Beckman Coulter, Inc.) Measurement conditions: The sample dispersion is added to 100 mL of the electrolyte to adjust the concentration so that the particle size of 30,000 particles can be measured in 20 seconds. Then, 30,000 particles are measured and the volume median particle size (D 50 ) is required.
[0143] [Circularity of toner particles (fused particles)] The circularity of the toner particles is measured under the following conditions. Measurement equipment: Flow-type particle image analyzer "FPIA-3000" (Sysmex Corporation) Preparation of dispersion: A dispersion of toner particles is prepared by diluting it with deionized water so that the solid content concentration becomes 0.001 to 0.05% by mass. Measurement mode: HPF measurement mode
[0144] [Volume median particle size of toner particles (D 50 ) and CV value Measuring instrument: "Coulter Multisizer (registered trademark) III" (manufactured by Beckman Coulter, Inc.) Aperture diameter: 50μm Analysis software: "Multisizer (registered trademark) III version 3.51" (Beckman Coulter, Inc.) Electrolyte: "Isoton (registered trademark) II" (manufactured by Beckman Coulter, Inc.) Dispersion liquid: Polyoxyethylene lauryl ether "Emulgen (registered trademark) 109P" (manufactured by Kao Corporation, HLB (Griffin) = 13.6) was dissolved in the electrolyte to adjust the concentration to 5% by mass. Dispersion conditions: 10 mg of the measurement sample is added to 5 mL of the dispersion liquid, and dispersed for 1 minute using an ultrasonic disperser (machine name: US-1, manufactured by SND Co., Ltd., output: 80 W). Then, 25 mL of electrolyte is added, and the mixture is further dispersed for 1 minute using the ultrasonic disperser to prepare a sample dispersion liquid. Measurement conditions: The sample dispersion was added to 100 mL of the electrolyte to adjust the concentration so that the particle size of 30,000 particles could be measured in 20 seconds. Then, 30,000 particles were measured, and the volume median particle size (D 50 ) is calculated according to the following formula: CV value (%) = (Standard deviation of particle size distribution / Volume average particle size) x 100
[0145] [Average particle size of external additives] The average particle size refers to the number-average particle size, and is calculated by measuring the particle sizes (average of major and minor diameters) of 500 particles in a scanning electron microscope (SEM) photograph and averaging these by number.
[0146] Resin manufacturing example 1 The alcohol component, carboxylic acid component, PET, esterification catalyst, and cocatalyst shown in Tables 1 and 2 were placed in a 10-liter four-neck flask equipped with a nitrogen inlet tube, a stirrer, and a thermocouple, and the mixture was held at 180°C for 1 hour under a nitrogen atmosphere, then heated from 180°C to 235°C at a rate of 10°C / h, and polycondensed at 235°C for 5 hours. The temperature was then lowered to 210°C, and the reaction was continued under a reduced pressure of 10 kPa until the softening points shown in Tables 1 and 2 were reached, to obtain amorphous polyester resins (resins A1 to A6, A11, and A12). The physical properties are shown in Tables 1 and 2.
[0147] Resin manufacturing example 2 The alcohol component, carboxylic acid component, PET, esterification catalyst, and cocatalyst shown in Tables 1 and 2 were placed in a 10-liter four-neck flask equipped with a nitrogen inlet tube, a stirrer, and a thermocouple, and the temperature was raised to 235°C under a nitrogen atmosphere, and polycondensation was carried out at 235°C for 6 hours. The temperature was then lowered to 210°C, and the reaction was carried out under a reduced pressure of 10 kPa until the softening points shown in Tables 1 and 2 were reached, to obtain amorphous polyester resins (resins A7, A10, and A13). The physical properties are shown in Tables 1 and 2.
[0148] Resin manufacturing example 3 The alcohol component, carboxylic acid component, esterification catalyst, and cocatalyst shown in Table 1 were placed in a 10-liter four-neck flask equipped with a nitrogen inlet tube, a dehydration tube equipped with a fractionating tube through which hot water at 98°C was passed, a stirrer, and a thermocouple, and the mixture was held at 180°C for 1 hour under a nitrogen atmosphere, then heated from 180°C to 235°C at a rate of 10°C / h, and then polycondensed at 235°C for 5 hours. The temperature was then lowered to 210°C, and the reaction was continued at 210°C under a reduced pressure of 10 kPa until the softening point shown in Table 1 was reached, to obtain amorphous polyester resins (resins A8 and A9). The physical properties are shown in Table 1.
[0149] [Table 1]
[0150] [Table 2]
[0151] Resin manufacturing example 4 The alcohol component and carboxylic acid component shown in Table 3 were placed in a 10-liter four-neck flask equipped with a thermometer, a stainless steel stirring rod, a downflow condenser, and a nitrogen inlet tube, and the temperature was raised to 200°C over 8 hours in a nitrogen atmosphere in a mantle heater. Then, an esterification catalyst shown in Table 3 was added, and the reaction was carried out at 8.0 kPa until the softening point shown in Table 3 was reached, obtaining crystalline polyester resins (resins C1 to C5, and resins C7 to C9). The physical properties are shown in Table 3.
[0152] Resin manufacturing example 5 The alcohol component, carboxylic acid component, and polymerization inhibitor shown in Table 3 were placed in a 10-liter four-neck flask equipped with a thermometer, a stainless steel stirring rod, a downflow condenser, and a nitrogen inlet tube, and the temperature was raised to 200°C over 8 hours in a nitrogen atmosphere in a mantle heater. Then, the esterification catalyst shown in Table 3 was added, and the reaction was carried out at 8.0 kPa until the softening point shown in Table 3 was reached, obtaining a crystalline polyester resin (resin C6). The physical properties are shown in Table 3.
[0153] [Table 3]
[0154] Example 1 [Preparation of Resin Dispersion] In a 3-liter vessel equipped with a stirrer, a reflux condenser, a dropping funnel, a thermometer, and a nitrogen inlet tube, 160 g of Resin A1, 40 g of Resin C1, and 200 g of methyl ethyl ketone were placed and dissolved for 2 hours at 73° C. A 5% by mass aqueous solution of sodium hydroxide was added to the resulting solution so that the degree of neutralization with respect to the acid value of the resin was 60 mol%, and the mixture was stirred for 30 minutes. Next, while maintaining the temperature at 73° C., 700 g of deionized water was added over 50 minutes while stirring at 200 r / min, and phase inversion emulsification was performed. While maintaining the temperature of the obtained solution at 73° C., methyl ethyl ketone was distilled off under reduced pressure to obtain a dispersion. Thereafter, while continuing to stir, the dispersion was cooled to 30° C., and deionized water was added so that the solid content concentration was 20 mass%, to obtain a resin dispersion (resin dispersion X1).
[0155] <Preparation of Colorant Dispersion> In a 1-liter beaker, 116.2 g of colorant "ECB-301" (Dainichiseika Color & Chemicals Mfg. Co., Ltd., Phthalocyanine Blue (PB15:3)), 154.9 g of anionic surfactant "Neopelex (registered trademark) G-15" (Kao Corporation, 15% by mass sodium dodecylbenzenesulfonate aqueous solution) and 260 g of deionized water were mixed and dispersed using a homogenizer at room temperature for 3 hours, and then deionized water was added so that the solids concentration became 20% by mass, thereby obtaining a colorant dispersion. The volume median particle diameter (D 50 ) was 118 nm and the CV value was 27%.
[0156] <Preparation of release agent dispersion> 50 g of a release agent (manufactured by Nippon Seiro Co., Ltd., trade name: FNP0090, Fischer-Tropsch wax, melting point: 90° C.), 5 g of a cationic surfactant (manufactured by Kao Corporation, trade name: Sanisol B50) and 200 g of deionized water were heated to 95° C., and the release agent was dispersed using a homogenizer, and then dispersed using a pressure discharge homogenizer, and deionized water was added to obtain a release agent dispersion with a solid content concentration of 20 mass %. The volume median particle diameter (D 50 ) was 550 nm and the CV value was 26%.
[0157] <Agglomeration process> Into a 3-liter four-neck flask equipped with a dehydration tube, a stirrer, and a thermocouple, 500 g of resin dispersion X1, 54 g of colorant dispersion, 35 g of release agent dispersion, and 3.3 g of 15% by mass sodium dodecylbenzenesulfonate aqueous solution "Neopelex G-15" (Kao Corporation, anionic surfactant) were placed and mixed at a temperature of 25° C. Next, while stirring the resulting mixture, a solution obtained by dissolving 43 g of ammonium sulfate in 980 g of deionized water and adding a 4.8% by mass potassium hydroxide aqueous solution to adjust the pH to 8.2 was added dropwise over 10 minutes at 25° C., and the temperature was then raised to 58° C. over 2 hours to measure the volume median particle diameter (D 50 The temperature was maintained at 58° C. until the particle diameter reached 6.2 μm, to obtain a dispersion of aggregated particles.
[0158] <Fusing process> To the obtained dispersion of aggregated particles, 22 g of sodium polyoxyethylene lauryl ether sulfate "EMAL E-27C" (Kao Corporation, anionic surfactant, effective concentration 27% by mass) and 1100 g of deionized water were added. The temperature was then raised to 75°C over 1 hour, and the temperature was maintained at 75°C until the circularity reached 0.970, thereby obtaining a dispersion of fused particles in which the aggregated particles were fused together.
[0159] The obtained dispersion of fused particles was cooled to 30°C, and the dispersion was suction filtered to separate the solid content, which was then washed with deionized water at 25°C and suction filtered at 25°C for 2 hours. The solid content was then vacuum dried at 33°C for 24 hours using a vacuum constant temperature dryer "DRV622DA" (manufactured by ADVANTEC) to obtain toner particles. The physical properties of the toner particles are shown in Table 5.
[0160] <External addition process> 100 parts by mass of toner particles, 2.5 parts by mass of hydrophobic silica "RY50" (manufactured by Nippon Aerosil Co., Ltd., average particle size: 40 nm, hydrophobic treatment agent: silicone oil), and 1.0 part by mass of hydrophobic silica "Cabosil (registered trademark) TS720" (manufactured by Cabot Corporation, average particle size: 12 nm, hydrophobic treatment agent: silicone oil) were placed in a Henschel mixer, stirred, and passed through a 150 mesh sieve to obtain a toner.
[0161] Examples 2 to 7, 10 to 15, 17 to 20 and Comparative Examples 1 to 4 The toner was obtained in the same manner as in Example 1 up to the external addition step, except that 160 g of the amorphous polyester resin and 40 g of the crystalline polyester resin shown in Table 4 were used as the binder resin to obtain resin dispersions (resin dispersions X2 to X7, X10 to X19, and X22 to X25).
[0162] Example 8 A toner was obtained by carrying out the same process up to the external addition step as in Example 1, except that the amount of resin A1 used was changed to 180 g and the amount of resin C1 used was changed to 20 g to obtain a resin dispersion (resin dispersion X8).
[0163] Example 9 A toner was obtained by carrying out the same process up to the external addition step as in Example 1, except that the amount of resin A1 used was changed to 140 g and the amount of resin C1 used was changed to 60 g to obtain a resin dispersion (resin dispersion X9).
[0164] Example 16 [Preparation of Resin Dispersion] (1) 200 g of Resin A1 and 200 g of methyl ethyl ketone were placed in a 3-liter vessel equipped with a stirrer, a reflux condenser, a dropping funnel, a thermometer, and a nitrogen inlet tube, and dissolved at 73° C. for 2 hours. A 5% by mass aqueous solution of sodium hydroxide was added to the resulting solution so that the degree of neutralization with respect to the acid value of the resin was 60 mol%, and the mixture was stirred for 30 minutes. Next, while maintaining the temperature at 73°C, 700g of deionized water was added over 50 minutes while stirring at 200r / min, and phase inversion emulsification was performed. The obtained solution was maintained at 73°C, and methyl ethyl ketone was distilled off under reduced pressure to obtain a dispersion. Thereafter, the dispersion was cooled to 30°C while continuing to stir, and deionized water was added so that the solid content concentration was 20% by mass, thereby obtaining a resin dispersion (resin dispersion X20).
[0165] (2) 200 g of resin C1 and 200 g of methyl ethyl ketone were placed in a 3-liter vessel equipped with a stirrer, a reflux condenser, a dropping funnel, a thermometer, and a nitrogen inlet tube, and dissolved at 73° C. for 2 hours. A 5% by mass aqueous solution of sodium hydroxide was added to the resulting solution so that the degree of neutralization with respect to the acid value of the resin was 60 mol%, and the mixture was stirred for 30 minutes. Next, while maintaining the temperature at 73°C, 700g of deionized water was added over 50 minutes while stirring at 200r / min, and phase inversion emulsification was performed. The obtained solution was maintained at 73°C, and methyl ethyl ketone was distilled off under reduced pressure to obtain a dispersion. Thereafter, the dispersion was cooled to 30°C while continuing to stir, and deionized water was added so that the solid content concentration was 20% by mass, thereby obtaining a resin dispersion (resin dispersion X21).
[0166] A toner was obtained by carrying out the same process up to the external addition process as in Example 1, except that in the aggregation process, 400 g of resin dispersion X20 and 100 g of resin dispersion X21 were used instead of resin dispersion X1.
[0167] For resin dispersions X1 to X25, the resin composition and the volume median particle size (D 50 ) and CV values are shown in Table 4.
[0168] [Table 4]
[0169] Test Example 1 [Low temperature fixability at high speed] Using a commercially available printer "Microline (registered trademark) 5400" (manufactured by Oki Electric Industry Co., Ltd.) on high-quality paper "J paper A4 size" (manufactured by Fujifilm Business Innovation Co., Ltd.), the amount of toner attached to the paper was 0.60 ± 0.01 mg / cm 2 The solid image was printed without fixing, leaving a margin of 5 mm from the top edge of A4 paper, and a length of 50 mm. Next, the same printer was prepared with a modified temperature-variable fixing unit, the temperature of the fixing unit was set to 100° C., and the toner was fixed on A4 sheets in portrait orientation at a speed of 0.8 seconds per sheet to obtain a printout. In the same manner, the temperature of the fixing unit was increased by 5° C. each time, and the toner was fixed to obtain a printed matter. A piece of mending tape, Scotch (registered trademark) Mending Tape 810 (manufactured by 3M Japan Ltd., width 18 mm), cut to a length of 50 mm was lightly applied from the upper margin of the printed image to the solid image, and then a 500 g weight (contact area 1963 mm 2) was placed on the print and pressed against it at a speed of 10 mm / s. The applied tape was then peeled off from the print at a peel angle of 180° from the bottom end at a speed of 10 mm / s. 30 sheets of high-quality paper "Excellent White Paper A4 Size" (manufactured by Oki Electric Industry Co., Ltd.) were placed under the print before and after the tape was applied, and the reflected image density of the fixed image portion of each print before and after the tape was applied was measured using a colorimeter "SpectroEye" (manufactured by GretagMacbeth, light irradiation conditions: standard light source D50, observation field of view 2°, density standard DINNB, absolute white standard), and the fixing rate was calculated from each reflected image density according to the following formula. Fixation rate (%) = (reflection image density after tape peeling / reflection image density before tape application) x 100 The lowest temperature at which the fixing rate was 90% or more was defined as the minimum fixing temperature, and the low-temperature fixing property was evaluated. The results are shown in Table 5. The lower the minimum fixing temperature, the better the low-temperature fixing property.
[0170] Test Example 2 [Low temperature fixability at normal speed] Except for changing the fixing speed to 2.0 seconds per sheet in the portrait direction of A4 paper, the low-temperature fixing property at normal speed was evaluated in the same manner as in Test Example 1. The results are shown in Table 5.
[0171] Test Example 3 [Toner Durability] The toner was loaded onto a printer called "Page Presto N-4" (Casio Computer Co., Ltd., fixing: contact fixing method, development: non-magnetic one-component development method, developer roll diameter: 2.3 cm), and a pattern of diagonal stripes with a blackening rate of 5.5% was continuously printed in an environment of 32°C temperature and 85% humidity. A black solid image was printed every 500 sheets during the printing process, and the presence or absence of streaks on the image was confirmed. Printing was stopped when streaks appeared on the image, and printing was continued up to a maximum of 9000 sheets. The number of sheets printed up to the point where streaks were visually observed on the image was regarded as the number of sheets on which streaks appeared due to the toner fusing and adhering to the developer roll, and durability was evaluated. The results are shown in Table 5. In the table, ">9000" means that no streaks appeared even on the 9000th sheet. The greater the number of sheets on which streaks did not appear, the higher the durability of the toner.
[0172] [Table 5]
[0173] From the above results, it is clear that all of the toners of Examples 1 to 20 are excellent in low-temperature fixability and durability during high-speed printing. In contrast, the toner of Comparative Example 1, which uses an amorphous polyester resin without PET, and the toner of Comparative Example 2, which uses an amorphous polyester resin directly using ethylene glycol, a monomer component of PET, are insufficient in durability. Also, the toner of Comparative Example 3, which uses a crystalline polyester resin with too low an ester group concentration, has good low-temperature fixability at normal speed, but is insufficient in low-temperature fixability during high-speed printing, and it is clear that the toners of Examples 1 to 20 have excellent low-temperature fixability that can withstand high-speed printing. The toner of Comparative Example 4, which uses a crystalline polyester resin with too high an ester group concentration, is lacking in durability. [Industrial Applicability]
[0174] The toner for developing electrostatic images obtained by the method of the present invention is used for developing latent images formed in electrophotography, electrostatic recording, electrostatic printing and the like.
Claims
1. A method for producing a toner for developing electrostatic images, comprising a step of aggregating resin particles, the resin particles containing a crystalline polyester resin C and an amorphous polyester resin A in the same or different particles, in an aqueous medium to obtain aggregated particles, wherein the crystalline polyester resin C has an ester group concentration of 6.5 mmol / g or more and 12.5 mmol / g or less, and the amorphous polyester resin A is a polycondensate of an alcohol component, a carboxylic acid component, and polyethylene terephthalate.
2. 2. The method for producing a toner for developing an electrostatic image according to claim 1, further comprising a step of fusing the aggregated particles obtained in the step of obtaining the aggregated particles to obtain toner particles.
3. 3. The method for producing a toner for developing electrostatic images according to claim 1, wherein the content of polyethylene terephthalate in the amorphous polyester resin A is 5 mol % or more and 75 mol % or less in the total amount of the alcohol component, the carboxylic acid component and the polyethylene terephthalate, assuming that a terephthalic acid-ethylene glycol unit is 1 mol.
4. 3. The method for producing a toner for developing electrostatic images according to claim 1, wherein the IV value of the polyethylene terephthalate is from 0.40 to 0.
80.
5. 3. The method for producing a toner for developing electrostatic images according to claim 1, wherein the content of the crystalline polyester resin C is from 3% by mass to 40% by mass in the total amount of the crystalline polyester resin C and the amorphous polyester resin A.
6. 3. The method for producing a toner for developing electrostatic images according to claim 1, wherein the alcohol component of the amorphous polyester resin A contains an aliphatic diol having 3 to 6 carbon atoms.
Citation Information
Patent Citations
Non-crystalline polyester resin, toner binder resin and toner for electrostatic image development
JP2019099699A
Toner particle using amorphous polyester resin
JP2021067882A